The answer to this question is A
Answer:
1. 20
2. 23
3. 6
Step-by-step explanation:
We have that:
f(x) = 2x
g(x) = x² + 1
f(g(x)) is the composite function of f and g. So
f(g(x)) = f(x²-1) = 2(x²+1) = 2x² + 2
1. f(g(3))
f(g(x)) = 2x² - 2 = 2(3)² + 2 = 18 + 2 = 20
2. f(3)+g(4)
f(3) = 2(3) = 6
g(4) = 4² + 1 = 17
f(3) + g(4) = 6 + 17 = 23
3. f(5) - 2g(1)
f(5) = 2(5) = 10
g(1) = (1)² + 1 = 2
f(5) - 2g(1) = 10 - 2*2 = 10 - 4 = 6
Answer:
V=75 in 3 9 in. 17 in. There are 1 more cubic inches of sand in the pyramid with the greater volume.
Step-by-step explanation:
Answer: 315.3 cm / 3.153 meters
Step-by-step explanation:
3,4 meters = 340 cm
340 cm - 24.7 cm = 315.3 cm
Good morning! So, what this question wants us to do is find each y value given its x value. Without the function it gives us already, this would be pretty difficult.
It gives us a function rule of y=2x+3. This means that we need to plug in each x value into the equation and solve for y. Let’s work on these first three.
y=2x+3} x=-4
y=2(-4)+3
y=-8+3
y=-5
So, if x=-4, then y=-5.
y=2x+3} x=-2
y=2(-2)+3
y=-4+3
y=-1
So, if x=-4, then y=-1.
y=2x+3} x=0
y=2(0)+3
y=0+3
y=3
So, if x=0, then y=3.
Try out the last one, and if you have any questions, comment below! Here are some extra x values if you need more practice.
Using the same function rule, y=2x+3, try to find the y value if x=-6, x=-3, x=5, or x=6.